Determination of Phosphate in Water Samples of Nashik District (Maharashtra State, India) Rivers by UV-Visible Spectroscopy - Sanjeevan J. Kharat; Sanjay D. Pagar (E-Journal of Chemistry)
The major rivers of Nashik District (Maharashtra State, India) are Godavari, Kadawa, Girna, Punad and Mosam. The major water pollutant of Nashik District Rivers is Phosphate. The amount of phosphate has been determined by the molybdenum blue phosphorous method in conjugation with UV-Visible Spectrophotometer. The data has been analyzed by least square method. The more phosphate polluted river in Nashik district is Godavari. The least phosphate polluted river in Nashik District is Punad.